PENGARUH PERCEIVED QUALITY, BRAND AWARENESS, BRAND IMAGE, BRAND TRUST TERHADAP PURCHASE INTETION PRODUK MAKANAN CEPAT SAJI DI INDONESIA - Sari, Wulan; Riorini, Sri Vandayuli; Agustina, Rita (JURSIMA, 2023)
This research aims to analyze the influence of Perceived quality, Brand awareness, Brand image, and Brand trust on Purchase intention for fast food products in Indonesia. The research uses quantitative methods by collecting data through questionnaire surveys. The independent variables in this research consist of Perceived Quality, Brand Awareness, Brand Image, and Brand Trust. Meanwhile, the dependent variable in this research is Purchase Intention. This research is included in correlational research. The data used is cross-sectional. Samples will be distributed using purposive sampling to fast food consumers in five big cities in Indonesia. The sample used in this research was 100 respondents. The collected data will be analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software. The research results show that there is a significant positive influence between Perceived quality, Brand awareness, Brand image and Brand trust on Purchase intention for fast food products in Indonesia.